Supramolecular approaches for insulin stabilization without prolonged duration of action - Rolande Meudom; Yanxian Zhang; Michael A. VandenBerg; Lei Zou; Yi Wolf Zhang; Matthew J. Webber; Danny Hung-Chieh Chou (Acta Pharmaceutica Sinica B, 2023)
Aggregation represents a significant challenge for the long-term formulation stability of insulin therapeutics. The supramolecular PEGylation of insulin with conjugates of cucurbit[7]uril and polyethylene glycol (CB[7]‒PEG) has been shown to stabilize insulin formulations by reducing aggregation propensity. Yet prolonged in vivo duration of action, arising from sustained complex formation in the subcutaneous depot, limits the application scope for meal-time insulin uses and could increase hypoglycemic risk several hours after a meal. Supramolecular affinity of CB[7] in binding the B1-Phe residue on insulin is central to supramolecular PEGylation using this approach. Accordingly, here we synthesized N-terminal acid-modified insulin analogs to reduce CB[7] interaction affinity at physiological pH and reduce the duration of action by decreasing the subcutaneous depot effect of the formulation. These insulin analogs show weak to no interaction with CB[7]‒PEG at physiological pH but demonstrate high formulation stability at reduced pH. Accordingly, N-terminal modified analogs have in vitro and in vivo bioactivity comparable to native insulin. Furthermore, in a rat model of diabetes, the acid-modified insulin formulated with CB[7]‒PEG offers a reduced duration of action compared to native insulin formulated with CB[7]‒PEG. This work extends the application of supramolecular PEGylation of insulin to achieve enhanced stability while reducing the risks arising from a subcutaneous depot effect prolonging in vivo duration of action.